2014
DOI: 10.1159/000363451
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular Adhesion Molecule-1 K469E and Angiotensinogen T207M Polymorphisms in Coronary Slow Flow

Abstract: Objective: To investigate intercellular adhesion molecule-1 (ICAM1) and angiotensinogen (AGT) gene polymorphisms, as related to atherosclerosis and endothelial dysfunction, in coronary slow flow (CSF). Subjects and Methods: The participants in this study were 48 patients with CSF and 67 patients with normal coronary flow as controls. The K469E polymorphism of ICAM1 (rs5498) and the T207M polymorphism of AGT (rs4762) were determined using the polymerase chain reaction amplification method. Results: Baseline dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…1 Although various mechanisms have been suggested for the pathogenesis of CSF, the pathophysiology and clinical implications of CSF are not clearly understood. [2][3][4] The effects of CSF, and subsequent inadequate blood supply, on myocardial functions are not known. Recent two-dimensional speckle tracking echocardiography (STE) and Doppler studies have shown that CSF results in systolic and diastolic dysfunctions.…”
mentioning
confidence: 99%
“…1 Although various mechanisms have been suggested for the pathogenesis of CSF, the pathophysiology and clinical implications of CSF are not clearly understood. [2][3][4] The effects of CSF, and subsequent inadequate blood supply, on myocardial functions are not known. Recent two-dimensional speckle tracking echocardiography (STE) and Doppler studies have shown that CSF results in systolic and diastolic dysfunctions.…”
mentioning
confidence: 99%
“…Second, Li et al [ 42 ] did not include 9 studies, [ 9 , 15 , 18 , 21 , 22 , 24 , 25 , 27 , 31 ] while Zou et al [ 43 ] did not include 11 studies. [ 9 , 14 , 15 , 18 , 21 , 22 , 24 27 , 31 ] Actually, these studies conformed to the inclusion criteria. Third, Li et al identified a Chinese study, [ 46 ] but we did not find the genotype numbers of rs5498 polymorphism in this study.…”
Section: Discussionmentioning
confidence: 99%
“…We thought our data were more robust than those of previous meta-analyses. More eligible studies were included in this meta-analysis [ 13 , 15 , 17 ]. In addition, the power analysis indicated that this meta-analysis had a power of 94.3% to detect the effect of rs5498 polymorphism on MI susceptibility with an OR of 0.60.…”
Section: Discussionmentioning
confidence: 99%